PENDEKATAN STEM BERBANTUAN DOTPLASMA UNTUK MENINGKATKAN HASIL BELAJAR BANGUN RUANG SISI DATAR - Novian Slamet Riyadi (Jurusan Pendidikan MIPA FKIP Universitas Jember, 2020)
Abstract: Using teaching media, an abstract concept in matematics can be presented concretely so the concept can be easier to be understood and comprehended by junior high school students. From the research finding there was an improvement on the students mastery in the bangun ruang sisi datar through Dotplasma mediausing STEM teaching model. Based on the research, the researcher recommends the teacher to use Dotplasma in teaching using STEM teaching model konsep Bangun Ruang Sisi Datar. Kata Kunci: Dotplasma, Pendekatan STEM, Hasil belajar